Determining Individuals’ Attitudes Toward Cancer Screening and Their Influential Factors - Erkal, Emre (UI Scholars Hub, 2022)
Background: Cancer screenings are of great importance for the early detection of cancer. The goal of this study is to determine the attitudes of individuals toward cancer screening and the factors affecting these attitudes. Methods: This descriptive, cross-sectional study comprised 1059 participants who were living in Turkey. The participants were recruited through the snowball sampling method between December 6 and 24, 2021. The Individual Self-Assessment Form and Attitude Scale for Cancer Screening were used to collect data. The data were analyzed by using independent samples t-test, one-way ANOVA, and Pearson’s correlation analysis. Results: The mean score of the participants’ attitude toward cancer screening was 94.57 ± 18.39. Age, gender, marital status, place of residence, family type, occupation, social security, income, and educational level had a significant effect on the participants’ attitude score (p < 0.05). Furthermore, the attitude score was significantly affected by cancer screening information; early cancer screening; and the beliefs that early cancer detection is achievable and that cancer is a preventable and treatable disease (p < 0.001). Conclusions: Individuals have a positive attitude toward cancer screening. Health professionals should inform individuals who have a negative attitude toward cancer screening.